WEAR BEHAVIOR OF DENTAL COMPOSITES - C, Sovitkar Abhinandan; Hambire, Dr. U. V. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
In this current study, three types of dental composites namely Tetric N-Ceram Ivoclar Vivadent,Coltene Brilliant NG and Voco Polofil NHT were comparatively evaluated on Pin on disc machine for wear rate analysis. The variables considered for the research work were Speed, load and sliding distance. Various combinations of these variables were made. Pre-experimentation was also carried to find out the most influencing values of these variables. The variables were so chosen that they would represent actual conditions under which the dental composites were supposed to work.The effect of three parameters such as Speed, load and sliding distance on Wear loss of three types of dental filler materials were examined. In this investigation, an effective approach based on Taguchi method, analysis of variance (ANOVA), multivariable linear regression (MVLR), has been developed to determine the optimum conditions leading to minimum Wear. Experiments were conducted by varying Speed, load and sliding distance using L9 orthogonal array of Taguchi method. After experimentation it was found that Tetric N-Ceram Ivoclar Vivadent has more sliding wear resistance as compare to Coltene Brilliant NG and Voco Polofil NHT dental composite.